Satisfaction on Educational Environment among Undergraduate Nursing Students - Budhathoki, Bamita; Thapa, Sajita (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Introduction: Dissatisfaction among undergraduate nursing students is a widespread concern across diverse educational settings, impacting their engagement, enjoyment, and essential skill development for nursing practice. Therefore, this study aimed to assess satisfaction on the educational environment among undergraduate nursing students in a college of Kathmandu. Method: A descriptive cross-sectional study was conducted with 126 undergraduate nursing students at Manmohan Memorial Institute of Health Sciences (MMIHS), Kathmandu, from 20th Jestha, 2081 to 32th Jestha, 2081 (June 2 -14, 2024 total enumerative sampling techniques was used to include all eligible B.sc. nursing students. Ethical approval was taken from the Institutional Review Committee (IRC) of NEHCO IRC and written consent was taken from respondents prior to data collection. Data was collected through self-administered questionnaire by using modified Nursing Student Satisfaction Scale (NSSS). Data was analyzed using SPSS version 23. Results: The study showed that students were most satisfied with Curriculum and Teaching (53.39%). Next was Professional Social Interaction (31.44%), and the least satisfaction was with the environment (15.17%). The overall average satisfaction score for the educational environment was 113.78 ± 24.81. There was a significant link between satisfaction with curriculum and teaching and the student’s age (p<0.05) and academic year (p<0.001). Satisfaction with the educational environment was also significantly related to academic year (p<0.001), residence, and cumulative GPA (p<0.05). Conclusion: Regarding the findings conclude that the environment subscale has the lowest mean score compared to the curriculum and teaching, as well as professional social interaction. The college could prioritize resource allocation to maintain and upgrade lab equipment, ensuring functionality and modernization.